Turning boxes into supportive circles: Enhancing online group work teaching during the COVID-19 pandemic. Issue 4 (2nd October 2021) - Saldanha, Kennedy; Currin-McCulloch, Jennifer; Muskat, Barbara; Simon, Shirley R.; Bergart, Ann M.; Mesbur, Ellen Sue; Guy, Donna; Chilwalo, Namoonga B.; Seck, Mamadou M.; Tully, Greg; Lind, Kristina; Lee, Cheryl D.; et al.
ABSTRACT: This paper reflects the collective experiences of fourteen internationally based social group work educators who met weekly and virtually for seven months during the transition to online teaching necessitated by the coronavirus pandemic. The meetings functioned as a mutual aid support group sponsored by the International Association of Social Work with Groups (IASWG). The paper discusses the group's perceptions of the essential components of effective online group work education. It begins with a review of the history of online social work education. It then outlines the key components instrumental in the planning and developing of engaged online group work classes. Topics include pre-course preparation, norm setting, and building community in the online classroom. Considerations related to the video conferencing platforms, course formats, activities, managing online fatigue, screen sharing, handling chat features, cameras, and break out rooms are interspersed throughout. The paper concludes with a discussion of the use of mutual aid groups as online teaching tools and highlights the online group work teaching experiences of two members in New Zealand and Namibia. Despite initial hesitancy to teach group work virtually, the authors recognize that this can be done effectively but requires additional planning and, ideally, peer and institutional support.